An approach to histone nearest neighbours in extended chromatin. - Hardison, R C (1975)
The primary sequence organization of histones upon the DNA molecule in chromatin has been analyzed by extension of the nucleoprotein at very low ionic strength and crosslinking with a reversible crosslinking reagent, methyl-4-mercaptobutyrimidate. Histones extracted after limited reaction were fractionated into different classes and the composition of the oligomers analyzed after reduction of the crosslinked material. We have found that the following dimers occur at a high frequency: (F3-F2b), (F3-F2a2), and (F2b-F2a2), whereas (F2b-F2al), (F3-F2al) and (F3-F3) occur with a lower frequency. F1 appears to polymerize rapidly to largely homogeneous polymers of high molecular weight. These results are analyzed in terms of several models proposed for chromatin structure.